2019
DOI: 10.1302/0301-620x.101b4.bjj-2018-1184.r1
|View full text |Cite
|
Sign up to set email alerts
|

Complications, reoperations, readmissions, and length of hospital stay in 34 639 surgical cases of lumbar disc herniation

Abstract: Aims The aims of this study were to determine the rates of surgical complications, reoperations, and readmissions following herniated lumbar disc surgery, and to investigate the impact of sociodemographic factors and comorbidity on the rate of such unfavourable events. Patients and Methods This was a longitudinal observation study. Data from herniated lumbar disc operations were retrieved from a large medical database using a combination of procedure and diagnosis codes from all public hospitals in Norway from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 21 publications
1
52
0
1
Order By: Relevance
“…Bleeding is one of the most common surgical complications of herniated lumbar disc surgeries (2). The blood loss under the endoscope during PELD is generally less than 10 ml, but there also can be massive bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bleeding is one of the most common surgical complications of herniated lumbar disc surgeries (2). The blood loss under the endoscope during PELD is generally less than 10 ml, but there also can be massive bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment for LDH include conservative therapy and surgery and the standard open discectomy has largely been replaced by microdiscectomy (1). According to a Norway longitudinal observation study of 34639 surgical cases of lumbar disc herniation, microdiscectomy was specified in 23929 patients (69%) (2). Percutaneous endoscopic lumbar discectomy (PELD) is one of the microdiscectomy methods which has made significant progress and is well accepted by surgeons in recent years with the development of endoscopic technique and surgical instruments (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The most common complications include dural tears (1%-4% of cases), 11,13,14,21,23 blood transfusions (2%-3% of cases), 14,21,23 and neural injuries (0.4% of cases). 21 None of the RCTs or prospective cohort studies reported cases of perioperative mortality, [11][12][13][14]17,[21][22][23][24][25] indicating that the risk of discectomy-related death is negligible. A recent (2019) analysis of 34 639 LDH operations performed over 15 years found that complications occurred in only 2.7% (95% confidence interval: 2.6%-2.9%) of cases, with no perioperative deaths.…”
Section: Summary Of the Clinical Evidence Discectomy Versus Nonsurgicmentioning
confidence: 99%
“…15 Based on a health technology assessment, which included a systematic literature review, public feedback, and voting from a clinical committee, the Washington State Health Care Authority requires at least 6 weeks of nonsurgical care unless progressive motor weakness is present. 16,17 Thus, the decision to continue nonsurgical care or undergo surgery considers the patient history, physical examination, radiological findings, and severity of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar disc herniation (LDH) accounts for a large proportion of low-back pain as it affects over 90% of individuals in their lifetime [1]. With an average onset age of 45 years, LDH usually occurs in people between 20 and 50 years of age and is relatively rare in the elderly [2]. LDH is often combined with ligamentum avum hypertrophy and lateral recess stenosis in older population, which lead to lumbar spinal stenosis (LSS) [3].…”
Section: Introductionmentioning
confidence: 99%